Ethical Issues in Medical Research & Publications - Islam, Quazi Tarikul; Rafiquddin, AKM (Journal of Medicine, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3329/jom.v7i2.1362 J MEDICINE 2006; 7 : 42-44